2020
DOI: 10.3390/pr8101212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rootstock and Harvesting Period on the Bioactive Compounds and Antioxidant Activity of Two Orange Cultivars (‘Salustiana’ and ‘Sanguinelli’) Widely Used in Juice Industry

Abstract: Oranges are a rich source of bioactive compounds with recognized benefits for human health. To guarantee high quality and production levels, citrus farms usually employ the combination of selected cultivars with well adapted rootstocks. This study analyzes the impact of four different citrus rootstocks (Forner-Alcaide no.5, ‘Cleopatra mandarin’, Citrus volkameriana and Carrizo citrange) on the bioactive compounds and antioxidant activity of two orange cultivars (‘Salustiana’ and ‘Sanguinelli’) widely used in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 55 publications
10
22
0
1
Order By: Relevance
“…According to our earlier results [16], the concentration of anthocyanins increased progressively during the sampling period. These authors detected the influence of rootstock on the accumulation of anthocyanins in the juice of the blood orange cultivar Sanguinelli.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…According to our earlier results [16], the concentration of anthocyanins increased progressively during the sampling period. These authors detected the influence of rootstock on the accumulation of anthocyanins in the juice of the blood orange cultivar Sanguinelli.…”
Section: Discussionsupporting
confidence: 69%
“…Several studies have documented the increase in anthocyanin content of pigmented oranges during ripening [17,38] but few in blood orange, as a function of rootstock [16]. A recent study demonstrates that some recently released rootstocks are better than others, with respect to the production of fruit with high levels of pigmentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids exert a potent antioxidant effect by removing free radicals through metal ion chelation, and by providing electrons or hydrogen atoms [42]. Anthocyanins belong to a subclass of flavonoids and remove free radicals, preventing the oxidation of cells [43]. Oxidation causes food decomposition, involving lipids, nutrients, and pigment destruction, so adding antioxidants to food packaging materials can extend the shelf life and improve quality [44].…”
Section: Antioxidant Activity Of Aronia Powders and Bioelastomersmentioning
confidence: 99%
“…Previous studies suggested that the regular intake of orange juice (OJ) reduces inflammatory reactions and oxidative stress. OJ flavanones, mainly naringenin-7-rutinoside and hesperetin-7-O-rutinoside, are reported to have a wide range of beneficial attributes on human health such as the improvement of lipid profile [37,38]. Garlic belongs to the Allium genus and is traditionally used as a medicinal plant all over the world.…”
Section: Plant-derived Bioactive Componentsmentioning
confidence: 99%